Kebebasan Hakim dalam Melahirkan Putusan Progresif - Akbar, Muhammad (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
Determining a decision is not easy and sometimes gives a difficult position for a judge, determining a judge's decision is required to carry out the technical juridical and procedural implementation of legislation. Therefore it becomes important to determine the conditions that must be owned by a judge related to his freedom in making progressive decisions. This research is a literature study to explore indicators that can produce a progressive decision that must be owned by a judge. The indicator that must be possessed is the independence of a judge, which is based on moral and ethical integrity, the transparency aspect of decisions is also a picture of freedom and progressiveness, besides that professionalism and intellectual ability are absolute requirements that are part of the basic things that a progressive judge must have.